Development of Project-Based Learning Integrated with Local Culture to Enhance Critical Thinking Skills of Students in Fine Motor Skills Development Course - Dwi Lyna Sari; Nesna Agustriana; Delrefi D; Lina Eka Retnaningsih (JCE (Journal of Childhood Education), 2024)
Students interest in local culture tends to decline, especially in the face of globalization's influence, which shifts cultural values. This study aims to develop a Project-Based Learning (PjBL) model integrated with local culture to enhance students' critical thinking skills in the course on the Development of Fine Motor Skills. This research is a development study or Research and Development (R&D) utilizing the 4D model (Define, Design, Development, and Dissemination). The research sample consists of third-semester students from the Early Childhood Education Teacher Program at Universitas Bengkulu for the 2024/2025 academic year. Data collection is conducted through interviews, observations, questionnaires, and documentation, while data analysis employs qualitative analysis methods. The results indicate that the local culture-based PjBL model meets the criteria of being valid, practical, and effective in improving students' critical thinking skills. This effectiveness is demonstrated through a three-phase trial showing significant differences in students' abilities before and after the implementation of PjBL. Future researchers are encouraged to implement the local culture-based PjBL model more broadly across various study programs and courses, as well as conduct further research to evaluate the long-term impact of PjBL implementation on the development of critical thinking skills and other learning aspects